Adaptive selective compressive sampling for sparse signal acquisition in noisy background. Issue 21 (1st October 2015) - Wen, Fangqing; Zhang, Yu; Zhang, Gong
Abstract : A new methodology for sparse signal acquisition using adaptive selective compressive sampling (ASCS) is presented. By employing the estimated prior information, the measurement matrix in the ASCS method can be adapted in order to selectively sense the sparse signal. The proposed ASCS method has an inherent characteristic of noise suppression, thus provides fewer noisy measurements. The experimental results demonstrate the effectiveness of the proposed scheme.